RETRACTED: Foreign Assistance, Sustainable Development, and Commercial Law: A Comparative Analysis of the Impact of Corruption on Developing Economies - Yu, Ying; Lihong, Huang; Mouneer, Salma; Ali, Hina; Munir, Arshad (Frontiers in Environmental Science, 2022)
The essential purpose of this research is to investigate the relationship between foreign assistance and economic growth. It also analyzes the role of corruption that might have influenced this relationship in aid recipient countries having a similar real gross domestic product (GDP) per capita but having different development patterns. For specific samples from 2000 to 2019, an analysis is performed. The model is split into three sections for this purpose. i.e., all developing economies, Sub Saharan Africa (SSA), and most corrupt countries from regions other than SSA. The difference Generalized Method of Moments (GMM) panel framework is used for empirical analysis. The study concludes that foreign aid does not show any encouraging and significant changes in overall economic growth in developing economies. In contrast, corruption has a powerful impact on foreign aid effectiveness. It is also observed from analysis that Sub-Saharan African (SSA) economies get a high level of foreign assistance but still cannot get maximum benefits due to different economic and social problems. Foreign assistance effectiveness is almost insignificant in most corrupt economies from other regions.